COMPARATIVE CHARACTERISTICS OF INTRODUCED RASPBERRY VARIETIES IN THE CONDITIONS OF POLISSIA OF UKRAINE - Hulko Б.; Hulko В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
In 2020, a primary variety study site was established to evaluate five new raspberry varieties: Meeker, Mapema, Pszehyba, Polonez, and Poemat. During the winter period, the researchers observed frost damage to the raspberry buds in all studied varieties. Among them, the Mapema variety demonstrated superior winter hardiness, while Poemat and Polonez exhibited medium winter hardiness. The Pszehyba variety was somewhat less resilient. After the growth period began, the overall condition of all studied plants was rated as good, scoring between 4 and 5 points. Damage caused by Didymella applanata did not exceed 1.9 points overall. The Poemat variety exhibited the least damage at 1.4 points, while the Pszehyba variety sustained the highest damage at 2.9 points. The Mapema variety's shoots were also affected, scoring 2.2 points, whereas Meeker and Polonez scored 1.8 and 1.9 points, respectively. Notably, the Poemat variety showed the greatest field resistance. Throughout the research, all raspberry varieties displayed signs of damage from Gloesporium venetum. Over the years of study, the Meeker variety produced the most shoots, averaging 22–25 shoots per linear meter, followed closely by Poemat with 20–25 shoots. The average shoot count for the Mapema variety ranged from 11 to 15, while the Pszehyba variety had 15 to 18 shoots per linear meter. In terms of shoot height, both the Przehyba and Poemat varieties reached 1.8 meters, while the Meeker variety was the tallest at 1.9 meters. The Polonez variety remained the shortest at 1.6 meters, although its height increased by an average of 10 centimeters compared to the previous year. Overall, the highest average shoot length over the two years of research was in the Meeker variety at 1.9 meters, while the Przehyba, Mapema, and Poemat varieties averaged 1.8 meters. The Polonez variety recorded the shortest average shoot length at 1.6 meters. The average berry weight varied significantly among the studied raspberry varieties. The Poemat variety had the smallest berries, weighing between 4.7 and 5.0 grams, with an average weight of 4.9 grams, which is quite high compared to zoned raspberry varieties that typically average 3.5 to 3.7 grams. The Meeker and Mapema varieties produced even larger berries, with an average weight of 5.3 grams. The Polonez variety also produced large berries, averaging between 5.7 and 6.2 grams, with an overall average of 6.0 grams. The Pszehyba variety was the standout for large fruit, with an average berry weight ranging from 7.6 to 9.1 grams, resulting in an average of 8.4 grams. Throughout the research period, total yield of the raspberry varieties ranged from 12.17 tons per hectare for the Polonez variety to 18.7 tons per hectare for the Pszehyba variety. The Pszehyba variety outperformed the Meeker control by 0.25 tons per hectare, and the Mapema variety surpassed it by 0.3 tons per hectare. In contrast, the Poemat and Polonez varieties fell short of the control by 1.49 and 4.03 tons per hectare, respectively.